332 Molecular Characteristics of Tumor Infiltrating Front in Glioblastoma: Insights Into Molecular Heterogeneity and Implications on Targeted Therapy. (August 2016) - Arimappamagan, Arivazhagan; Kruthika; Dawn, Rose; Paturu, Kondaiah; Santosh, Vani
Abstract : INTRODUCTION: Molecular heterogeneity in glioblastoma (GBM) is a novel area of research recently. Because tumor infiltrating front in GBM is often left behind following tumor decompression, knowledge of its genetic makeup can improve the rationale of potential molecular targets. METHODS: MRI localized biopsies of the tumor core and peritumoral brain zone (PBZ) were obtained from 25 GBM patients. The PBZ samples containing 15% to 30% tumor cells and core samples with predominantly tumor cells along with 8 nonneoplastic brain tissues were selected for a whole Genome Gene Expression Microarray. The list of differentially expressed genes between the tumor core and PBZ compared with nonneoplastic brain tissue was identified using R Bioconductor. Selected genes were validated using quantitative real-time polymerase chain reaction (PCR) and immunohistochemistry (IHC). RESULTS: Unsupervised hierarchical clustering of the genes revealed that the tumor core and PBZ samples showed a varied gene expression profile and clustered into 2 distinct groups. Approximately 7123, 5188, and 991 genes were differentially expressed in Core vs Normal, PBZ vs Normal and PBZ vs Core. Novel genes like PBK (role in cell cycle), MELK (stem cell marker), and TOP2A (proliferation marker) were upregulated in PBZ and tumor core compared with normal brain and robustly validated on IHC. Pathways involved in cell cycle, immune response, cell-cell adhesion, cell-matrix interaction, etc, were commonly enriched in periphery and tumor core compared with normal brain. Some of the novel markers were validated by real-time PCR and IHC. CONCLUSION: We demonstrate that the key genes involved in tumor cell proliferation, invasion, migration, response to immune system, and stemness markers are highly enriched in the PBZ. These genes, probably contribute to the resistance of PBZ cells to standard adjuvant therapy, resulting in tumor recurrence.